Konstruktion und empirische Überprüfung der Güte eines Beobachtungsrasters zum Erkennen besonderer mathematischer Begabung im Grundschulalter im Rahmen eines Talentsucheprozesses (mathematica didactica, 2021)
One possible tool for identifying promising students are checklists. Critical discussions ask whether they are suitable for this task. For this research task specific checklists are used with the aim to give observers hints about heuristics used by mathematical promising students. Firstly, a theoretical introduction into the field of mathematical giftedness and questions about identification of mathematical giftedness at the age of primary grade students is given. Afterwards follows a description of the development of checklists based on progressive research problems. Within the framework of a talent search process for mathematical promising third grade students their suitability is proved. That about 90 % of the students are assessed appropriate supports the assumption that the instrument is suitable as part of an identification process.